GROUP COLLABORATIVE CHALLENGES IN TODAY’S - Campbell, Mr. Andrew (IJRDO - Journal of Applied Management Science, 2016)
This paper examines the collaborative challenges of organizational intergroup and intergroup dynamics. Research shows that collaborative networks are a strategic asset used by firms that form as alliances and partnerships to develop new products and services in sustaining a competitive advantage (Provan & Kenis, 2007). This paper argues that collaborative relationships are challenging. The challenge of leader-follower relationships, group members that represent organizational interests, transnational coordination, and intergroup conflict compounds the firm’s collaboration outcomes. The author addresses negotiation strategies for problem solving, and conflict resolution to enhance collaborative efforts within the organization.